Dengue Hemorrhagic Fever (DHF) Behavior to Prevent - Damanik, Hanna DL; Indri Astuti; Kamsul (Universitas Airlangga, 2023)
Background: Dengue Hemorrhagic Fever (DHF) is a disease caused by a virus that is transmitted by female mosquitoes, especially from the Ae. aegypti species. Knowledge and attitude factors are factors that influence the prevention of DHF. Purpose: To find out the knowledge, attitudes, and practices of the community in preventing DHF and the relationship between knowledge and attitudes, knowledge and practice, and attitude and practice. Methods: This study used a cross-sectional design. The research location was Kelurahan 30 Ilir, Palembang City which consists of RT.11 and RT.16. The population in this study was housewives with a sample of 95 respondents using a purposive sampling technique. The data were collected by interview using a questionnaire. Results: The results of statistical analysis showed that there was a relationship between knowledge and practice in DHF prevention measures (p-value = 0.006), there was no relationship between knowledge and attitudes in DHF prevention measures (p = 0.480), attitudes and practice in DHF prevention measures (p = 0.723). Providing education to the community is important to do as an effort to increase DHF prevention behavior. Conclusion: DHF prevention behavior comprising the aspects of knowledge, attitudes, and practices was good and there was a significant relationship between knowledge and DHF prevention measures.